1992
DOI: 10.1021/bi00129a015
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR comparison of noncovalent and covalently cross-linked complexes of cytochrome c peroxidase with horse, tuna, and yeast ferricytochromes c

Abstract: Proton NMR spectroscopy at 500 and 361 MHz has been used to characterize the noncovalent or electrostatic complexes of yeast cytochrome c peroxidase (CcP) with horse, tuna, yeast isozyme-1, and yeast isozyme-2 ferricytochromes c and the covalently cross-linked complexes of cytochrome c peroxidase with horse and yeast isozyme-1 ferricytochromes c. Under the conditions employed in this work, the stoichiometry of the predominant complex formed in solution (which totaled greater than 90% of complex formed) was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
42
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 71 publications
22
42
1
Order By: Relevance
“…From these calculations, we conclude that the proteins spend Ͼ70% of the lifetime of the complex in the dominant orientation. This finding is consistent with other studies that have proposed the existence of a single-orientation complex in solution (10,34,35). In particular, large NMR chemical-shift perturbations of Cc resonances upon complex formation suggest the presence of a dominant orientation (30) because for more dynamic protein complexes, the perturbations tend to be smaller (36,37).…”
Section: Materials and Methods)supporting
confidence: 92%
See 2 more Smart Citations
“…From these calculations, we conclude that the proteins spend Ͼ70% of the lifetime of the complex in the dominant orientation. This finding is consistent with other studies that have proposed the existence of a single-orientation complex in solution (10,34,35). In particular, large NMR chemical-shift perturbations of Cc resonances upon complex formation suggest the presence of a dominant orientation (30) because for more dynamic protein complexes, the perturbations tend to be smaller (36,37).…”
Section: Materials and Methods)supporting
confidence: 92%
“…The presence of multiple orientations within Cc-CcP complex previously has been suggested by several studies (9)(10)(11)(12)(13)(14)(15)17). A complex comprising an equilibrium between a well defined form and a dynamic state (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The resonance of heme methyl 3 is strongly downfield-shifted in yeast cytochrome c when it binds to the yeast peroxidase, whereas that of heme methyl 8 experiences a small upfield shift (27,28). Perturbations of the heme methyl resonances of horse cytochrome c are much smaller (29) and indeed can be mimicked by binding of polyglutamate (30).…”
Section: Discussionmentioning
confidence: 99%
“…Early NMR spectroscopy studies have demonstrated that the dissociation rate of the complex is concentration dependent (Moench et al, 1992;Yi et al, 1994a), indicating that complex formation is not a simple bimolecular process. The first two-dimensional mapping of the binding site on Cc was performed by taking advantage of the protection against solvent exchange of amide protons in the interface upon complex formation.…”
Section: A Model For Complex Formationmentioning
confidence: 99%